Socio-economic backgraound of "high achievers" as compared to "low achievers" in the elementary schools - Olarte, Jose M. 1925- (1970)
The purpose of the study is to compare the socio-economic background of "high achievers" and "low achievers" relative to parents' place of birth and age, employment, educational attainment, occupation, recreational activities, participation in group activities, religious affiliation, size of family, family income, cultural possessions, and material possessions. Results of the study provide insights on some socio-economic variables which may account for the level of pupil achievement.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Dona Aurora, Elementary School, Baguio City -- Students; Ilang Elementary School, Benquet -- Students; Home and school